The Relationship Between Nurses’ Work Effectiveness and Work Engagement - Tahmine Salehi; Iman Khosravi; Shima Haghani (Journal of Client-centered Nursing Care, 2023)
Background: Nurses significantly contribute to the healthcare system, constituting the highest number of healthcare staff. A positive attitude or mindset at work increases the ability to carry out the organization’s duties, tasks, and plans. This study investigates the relationship between work effectiveness and work engagement of nurses in the selected hospitals affiliated with Iran University of Medical Sciences (IUMS), Tehran City, Iran, in 2021. Methods: This descriptive cross-sectional study has employed a correlational design. A total of 255 nurses working in selected hospitals affiliated with IUMS were recruited through proportionate stratified sampling. The study data were collected using the utrecht work engagement scale (UWES) and conditions for work effectiveness questionnaire II (CWEQ-II). Statistical analyses involved descriptive statistics, the independent t-test, analysis of variance, the Pearson correlation, and regression in SPSS software, version 22. The significance level was set at P<0.05. Results: The Mean±SD work effectiveness among nurses was found to be 37.31±7.41, indicating their medium-to-high work effectiveness. Also, their Mean±SD work engagement was 68.96±15.48, indicating the high work engagement of nurses. There was also a significant positive relationship (r=0.656, P<0.001) between the total work effectiveness score and work engagement. The results showed that the “support” dimension of work effectiveness exhibited the highest correlation with work engagement (r=0.606, P<0.001). Also, the “absorption by work” dimension of work engagement had the highest correlation with work effectiveness (r=0.653, P<0.001). Conclusion: According to the study results, increasing the work effectiveness of nurses necessitates the creation of a positive attitude and perspective through managerial actions.